Effects of chloride transport properties in nano metaclayed ultra-high performance concrete towards corrosion characteristics of embedded steel / Mohd Faizal Md Jaafar - Md Jaafar, Mohd Faizal (2019)
The major concern on the deterioration of reinforced concrete structure is due to the corrosion of steel reinforcement from the aggressive environment such as chloride penetration. Ultra-high performance concrete (UHPC) is an advanced concrete material having ultra-high strength with excellent durability properties. Inclusion of nano metaclay in UHPC is expected to overcome the chloride penetration resulting corrosion of steel embedded in UHPC by providing nano filler effect. In this study, chloride penetration resistance characteristics of concrete and corrosion steel embedded in concrete specimens were investigated. Four (4) types of concrete were cast namely normal performance concrete (NPC), high performance concrete (HPC), ultra-high performance concrete (UHPC) and a series of nano metaclayed-UHPC. The raw nano clay underwent the calcination process to produce nano metaclay and its chemical composition and morphology properties were determined by using X-Ray Diffraction (XRD) and Scanning Electron Microscope (SEM), respectively. The nano metaclayed- UHPC mixes were designed based on 1%, 3% and 5% levels of replacement of nano metaclay to Ordinary Portland Cement (OPC).